Pengaruh Kepribadian Big Five Dan Coping Stress Terhadap Kecerdasan Emosi Pada Mahasiswa Kedokteran Di Jakarta - Ridha Hanifah Margolang; Risatianti Kolopaking (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2017)
This study was conducted to know the significance influence of the big five personality (extraversion, agreeableness, conscientiousness, openness, neuroticism) and coping stress (confrontive coping, distancing, self-control, social support accepting responsibility, escape avoidance, planful problem solving, positive reappraisal) towards emotional intelligence. Participants in this study are medical students of State and Private Universities in Jakarta who are undergoing pra-clinic / Co- Assistant period from the 8th to 11th semester and taken by snowball sampling technique. The CFA technique (Confirmatory Factor Analysis) was used to test the validity of the measuring instrument and multiple regression analysis was used to test the research hypothesis. The results showed that the big five personality variable and coping stress had a significant influence towards emotional intelligence. A large proportion of the variance of emotional intelligence that is explained by all independent variables of 63.5%, while the remaining 36.5% are influenced by other variables outside this research. There are six variables that have significant effect on emotional intelligence which is agreeableness, openness, self control, social support, planful problem solving, positive reappraisal. Meanwhile, the variables of extraversion, consciencetiousness, neurotiscm, confrontive coping, distancing, accepting responsibility, escape avoidance, has no significant effect on emotional intelligence. Researcher suggest that all medical faculty creates emotional intelligence as an additional course so they can understand and practice how to control their emotions properly. DOI: 10.15408/tazkiya.v22i2.8410